Prediction of metal ion ligand binding residues by adding disorder value and propensity factors based on deep learning algorithm - Hao, Sixi; Hu, Xiuzhen; Feng, Zhenxing; Sun, Kai; You, Xiaoxiao; Wang, Ziyang; Yang, Caiyun (Frontiers in Genetics, 2022)
Proteins need to interact with different ligands to perform their functions. Among the ligands, the metal ion is a major ligand. At present, the prediction of protein metal ion ligand binding residues is a challenge. In this study, we selected Zn2+, Cu2+, Fe2+, Fe3+, Co2+, Mn2+, Ca2+ and Mg2+ metal ion ligands from the BioLip database as the research objects. Based on the amino acids, the physicochemical properties and predicted structural information, we introduced the disorder value as the feature parameter. In addition, based on the component information, position weight matrix and information entropy, we introduced the propensity factor as prediction parameters. Then, we used the deep neural network algorithm for the prediction. Furtherly, we made an optimization for the hyper-parameters of the deep learning algorithm and obtained improved results than the previous IonSeq method.